Pyrrolizidine alkaloids: occurrence, biology, and chemical synthesis. Issue 1 (26th October 2016) - Robertson, Jeremy; Stevens, Kiri
Abstract : This review focuses on the isolation, biological activity, metabolism, and (bio)synthesis of natural products containing a 1-azabicyclo[3.3.0]octane core (January 2013 to December 2015). Abstract : Covering: 2013 up to the end of 2015 This review covers the isolation and structure of new pyrrolizidines; pyrrolizidine biosynthesis; biological activity, including the occurrence of pyrrolizidines as toxic components or contaminants in foods and beverages; and formal and total syntheses of naturally-occurring pyrrolizidine alkaloids and closely related non-natural analogues.